EFEKTIVITAS PELAKSANAAN KURIKULUM PADA MADRASAH TSANAWIYAH: OBSERVASI MENDALAM DI MTSN 2 PADANG PARIAMAN - Halimah Sutri; Yulianis Yulianis (Ensiklopedia of Journal, 2026)
Curriculum implementation in madrasas often faces a gap between planning documents and learning practices, so an empirical study is needed to see the effectiveness of its implementation in the field; this condition is the background to the research at MTsN 2 Padang Pariaman as a state madrasa that actively implements the Merdeka Curriculum and part of the 2013 Curriculum. This study uses a descriptive qualitative method with data collection techniques through non-participant observation of learning activities, semi-structured interviews with the madrasah principal, curriculum representatives, and teachers, as well as documentation analysis of Prota, Promes, teaching modules, assessments, and curriculum management documents; all data are analyzed using an interactive model through the stages of reduction, presentation, and drawing conclusions. The results of the study indicate that curriculum planning has been carried out systematically through the preparation of teaching materials, integration of religious values and the Pancasila Student Profile, and the implementation of diagnostic assessments; the implementation of learning is quite effective with the use of active methods, digital media, differentiated learning, and strengthening Islamic character; Meanwhile, evaluation was conducted through formative, summative, and portfolio assessments, although challenges remained in the consistency of remedial measures, variety of learning media, and academic supervision. These findings confirm that curriculum implementation at MTsN 2 Padang Pariaman is in the effective category but still requires optimization to continuously improve learning quality. Keywords:  Curriculum implementation; learning effectiveness; MTsN 2 Padang Pariaman